Digitalized Electronic Voting System - Dukka Bindu Venkata Raghav; Sunith Kumar Bandi (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
In the present scenario, Electronic Voting Machines ("EVM") are being used in India, generally for state elections. These EVMs are being used since 1999 upto till date. The EVMs reduce the time for both casting a vote and declaring the results when compared to the old paper ballot systems, up to 2004 there is no Tampering and security provided for EVMs after 2004 Supreme court and Election Commission decided to introduce EVMs with Voter Verified Paper Audit Trail(VVPAT) system but it also having some difficulties like missing of names in the voter list, requirement of huge manpower, storing of EVMs for counting purpose etc, so our proposed method is useful to overcome above problems in the voting system by using the Biometric and Aadhaar  information.